AB0861 Prognostic Value of Ana Positivity in Greek Adult JIA Patients. (15th July 2016) - Dimopoulou, D.; Trachana, M.; Pratsidou, P.; Sidiropoulos, P.; Tzimouli, V.; Kanakoudi-Tsakalidou, F.; Garyfallos, A.
Abstract : Background: Antinuclear antibodies (ANA), one of the biomarkers of ILAR JIA classification, has been proposed to be associated with a protracted disease course overtime, regardless of JIA subtype. However, their role in the disease outcome is still debated. Objectives: To investigate the impact of ANA positivity in the long-term outcome of JIA patients. Methods: Patients ≥18 years with an established JIA, a minimal disease duration of 5 years and no history of a >6–month care from external rheumatologists, were enrolled in the study. Data were retrieved from the patients' charts, including ANA titers at onset (2 measurements, 3 months apart). The ANA were measured by indirect immunofluorescence (cut-off value ≥1:160). Clinical, laboratory -including ANA- and radiographic assessment were performed at the last follow-up visit, 17.2 years post-diagnosis. The outcome variables defined were: radiographic damage assessed by the total modified Sharp/van der Heijde Score (TmSvdHS), articular and extra-articular damage by Juvenile Arthritis Damage Index (JADI-A and JADI-E), physical ability by the Health Assessment Questionnaire-Disability Index (HAQ-DI) and the cumulative % times spent in a state of disease activity and of clinical remission off medication (CR). Results: Hundred two patients (72 females) were enrolled. The disease age of onset (mean ±SD) was 7.7±4 years, the interval from onset to last visit 17.2±6.7 years and the patients' current age 25±5.9 years. Thirty three (32.4%) patients were ANA positive at onset. At the last follow-up, there was no significant difference between ANA positive and ANA negative patients in terms of TmSvdHS (p=0.982), JADI-A (p=0.699), JADI-E (p=0.235), HAQ-DI (p=0.234), cumulative % time spent in disease activity (p=0.583) or CR (p=0.175). There was no statistical gender difference among ANA positive patients (F:M 36.6%:25%, p=0.385), but they had an earlier disease onset (p=0.038), mostly oligoarticular (p=0.004) and were more prone to uveitis development (p=0.001). In the multivariate analysis ANA positivity was found to be the single independent risk factor for uveitis development [OR (95%) 10.703 (1.821, 62.899), p=0.009]. Conclusions: Patients with ANA positive had predominantly an earlier and oligoarticular disease onset and a higher risk of uveitis development. However, ANA positivity was not found to influence the final disease outcome in terms of articular and extra articular degree of damage, radiographic abnormalities, physical disability and cumulative % time spent in disease activity or CR. References: Martini et al.(2010). Ann Rheum Dis. 69:1260–3, Ravelli et al.(2011) Arthritis Rheum. 63:267–75. Disclosure of Interest: None declared